Framing the ASEAN Charter : An ISEAS Perspective - Severino, Rodolfo (Book collections on Project MUSE., 2005)
In this booklet, the Institute of Southeast Asian Studies has put together some ideas for the proposed ASEAN Charter. The leaders of the Association of Southeast Asian Nations had endorsed the concept of a charter for the association on the conviction that such a document would help in making ASEAN a more robust force for peace and stability, a more deeply integrated and more competitive economic community, a more effective instrument for regional cooperation, and a worthier vessel for the h ...